Walking Methodologies with/in Teacher Education - Franklin-Phipps , Asilia; Gleason , Tristan (Journal of Public Pedagogies, 2019)
This essay begins with the limitations of reflection in teacher education practitioner research. We wonder about the confines of a reflective practice that is solitary, ahistorical, and written in a particular academic register with an audience of one in mind. Instead, we explore the potential of walking methodologies as critical praxes with a group of pre-service educators. To do so we take a walk that is collective and focused on the way history is entangled with the students’ multimodal responses to this experience. We argue that walking as reflective praxis produces different possibilities in the space of teacher education. Pre-service educators participated in a mode of public pedagogy that challenges the treatment of teaching and learning as ahistorical and universal processes that can be neatly represented by the written word.